Diffusion bonding between Ti-6Al-4V alloy and ferritic stainless steel - Kurt, Bulent; Orhan, Nuri; Evin, Ertan; Calik, Adnan (Elsevier, 2007)
In the present study, Ti-6Al-4V alloy was diffusion bonded to a ferritic stainless steel. The effect of bonding temperature on the microstructural development across the joint region was investigated. After diffusion bonding, microstructural analysis including metallographic examination, energy dispersive spectrograph (EDS) and shear strength was conduced. From the results, it was seen that bonding on the temperature was affecting the Fe and Ti mutual diffusion which controls the interface microstructure. The microstructure of the interface region was formed, consisting of Fe and Ti intermetallics. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: diffusion bonding; Ti-6Al-4V; ferritic stainless steel; interface microstructure